Pengaruh Pembiayaan Mitraguna Berkah Dengan Akad Murabahah Terhadap Kesejahteraan Pegawai Negeri Sipil Kabupaten Aceh Singkil - Riki Pranata; Waizul Qarni (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Banking institutions have the function of collecting and distributing public funds, with reference to the BSI KCP Singkil bank with a sharia system that uses a murabaha contract, so that the existence of partner-to-blessing financing as a welfare effort for Civil Servants (PNS), causes controversy with the concept of conventional banks with a system interest with its murabahah concept. This study aims to determine the financing of Mitraguna Blessing with a murabaha contract for the welfare of Civil Servants (PNS) of Aceh Singkil Regency in Islamic banking. This research is a type of field research (field research) which is descriptive qualitative, data collection using interview techniques Bank BSI KCP Singkil. The results of this study: 1). Most customers from civil servants in Aceh Singkil district take out the BSI Singkil blessing partnership financing with the aim of improving their lives, such as building a place of business, buying garden land, building a house, renovating a place of business or renovating a house and buying a vehicle. 2). Mitraguna Berkah Financing with a Murabahah Agreement Bank Syariah Indonesia, Tbk. for civil servants at the stage of the disbursement process, the use of this murabaha contract is in accordance with the legal basis both in sharia and positive law.